Anti-Inflammatory Function Analysis of Lacticaseibacillus rhamnosus CP-1 Strain Based on Whole-Genome Sequencing - Hanyu Chu; Lijie Zhou; Yanzhen Mao; Ren Liu; Jiaojiao Han; Xiurong Su; Jun Zhou (BioTech, 2025)
Lacticaseibacillus rhamnosus (L. rhamnosus) is a safe probiotic with no side effects, providing benefits such as gut microbiota regulation and immune enhancement, making it highly valuable with strong potential. However, strains from different sources have unique traits, and whole-genome sequencing (WGS) helps analyse these differences. In this study, we used WGS to examine L. rhamnosus strains from mice with fish oil-treated smoking-induced pneumonia to better understand their biological functions and explore possible anti-inflammatory mechanisms. Methods: We isolated a strain, Lacticaseibacillus rhamnosus CP-1 (L. rhamnosus CP-1), from mice intestines where fish oil alleviated smoking-induced pneumonia. Identification of probiotic-related genes by WGS and characterised the strain’s probiotic properties. Results: L. rhamnosus CP-1 has a single circular chromosome (2,989,570 bp, 46.76% GC content) and no plasmids. COG, GO, and KEGG databases revealed genes linked to carbohydrate metabolism. The CAZy database identified GH25 lysozyme and PL8 polysaccharide lyase genes. KEGG highlighted an antimicrobial peptide ABC transporter permease, while TCDB noted the ABC-type antimicrobial peptide transporter (the main active transport component). KEGG also showed 10 genes for terpenoid skeleton biosynthesis and 5 for keto-glycan unit biosynthesis. Additionally, L. rhamnosus CP-1 carries metabolic regulators and bacteriocin-related genes. Conclusions: Whole-genome sequencing analysis revealed that L. rhamnosus CP-1 has carbohydrate utilisation and potential anti-inflammatory effects at the molecular level. Potential functional genes include carbohydrate transport and hydrolase, antimicrobial peptide ABC transporter and its osmotic enzyme components, bacteriocin immune protein, terpenoid skeleton, and keto-glycan synthesis.